2013
DOI: 10.1080/02773813.2013.768672
|View full text |Cite
|
Sign up to set email alerts
|

Increased Water Resistance of Bamboo Flour/Polyethylene Composites

Abstract: To improve the water resistance of bamboo flour/high-density polyethylene (HDPE) composites, the effects of "plastic content," "coupling agents," and the "addition of micro-fibrillated cellulose (MFC)" on formulations were studied, and their rheological and mechanical properties were evaluated. The composites were prepared by injecting molding with a basic composition of equivalent amounts of bamboo flour and HDPE, and the melting fluidity of the compounds, tensile strength, and tensile modulus of the composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…6,7 However, hydrophilic cellulose nanober lm adsorbs water under hydrothermal conditions, which strongly affects its surface behavior and can lead to reliability problems. 8,9 Consequently, the water adsorption mechanisms of cellulose nanober lm need to be fully understood in order for this sustainable raw material to be efficiently utilized.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, hydrophilic cellulose nanober lm adsorbs water under hydrothermal conditions, which strongly affects its surface behavior and can lead to reliability problems. 8,9 Consequently, the water adsorption mechanisms of cellulose nanober lm need to be fully understood in order for this sustainable raw material to be efficiently utilized.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that the mechanical properties and water resistance of bamboo flour/highdensity polyethylene (HDPE) composites are enhanced by the addition of micro-fibrillated cellulose prepared by wet ball-milling commercial cellulose powder. [7] Mechanical dry grinding pulverizes cellulosic materials into fine particles, and prolonged pulverization leads to increased flocculation. [8] Excessive pulverization of the wood flour by dry ballmilling had a negative effect on the mechanical properties of the WPC made with it.…”
Section: Introductionmentioning
confidence: 99%
“…WF formed by ball-milling is also used to produce WPCs [11][12][13]. The tensile and flexural strengths of WPCs containing wet ball-milling WF had high strength by surface fibrous structure on WF [11,12]. The strength did not improve in the WPCs containing dry ball-milling WF [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies, milled WF was vacuum-and freeze-dried [11][12][13]. During heat drying, WF becomes easily aggregated through rapid water vaporization.…”
Section: Introductionmentioning
confidence: 99%